A Novel Pyridyl Ester Isolated from Leucas cephalotes - Priya, K. Kavitha; Anuradha, V. (Asian Journal of Chemistry, 2019)
From the flowers of Leucas cephalotes, pyridine-3-carboxylic acid ester was isolated. Its structure was established as 2′,5′-dihydroxy-3′-pyridyl-(2,5-dihydroxy)pyridinyl-3-carboxylate on the basis of spectroscopic analysis. To out best of knowledge, this is the first report from Leucas cephalotes in particular and Labiatae family in general.